Analysis of factors that motivate and prevent the blood donation decision among the medical college students - R., Chandrashekhar; Basagoudar, Shashidhar S.; Hatnoor, Shivappa; Kirte, Rahul C. (International Journal Of Community Medicine And Public Health, 2018)
Background: Human blood is an essential element of human life. Medical colleges students can be very good source for voluntary blood donation. This study was done with the objectives - to find out the factors motivating blood donation and the factors responsible for not donating the blood among the medical students. Methods: A cross sectional study was conducted among the students of a government autonomous medical college, situated at northern part of Karnataka, India. Data was collected by a pre tested, semi structured, self administered, questionnaire. All the students studying MBBS in RIMS, Raichur who have joined the course between 2013 -2016 were included in the study. Results: In our study a total of 319 students have participated. Among the total students studied 85 (26.64%) have donated the blood at least once and 234 (73.36%) students have not donated even once. The major motivating factor for voluntary blood donation as responded by students was altruism/ doing good to others (51.8%). Major reason for non-donation of blood was he/she was never been asked for blood donation (56.4%). In the present study, the voluntary blood donation was significantly high among males (40.3%) compared to females (8.7%). Proportion of people who have donated blood increased with each year of study, highest among MBBS phase III Part 2 (53.6%). Conclusions: Having knowledge and attitude alone will not improve the voluntary blood donation unless, blood donation opportunity is available. So creating opportunities for donation of blood through voluntary blood donation drives is very much needed.